Effect of Yam Flour Modified with Plasma-Activated Water Combined with Extrusion Treatment on the Quality of Chinese Noodles - Miaomiao Shi; Yirui Chen; Xiaopei Zhu; Xiaolong Ji; Yizhe Yan (Foods)
Yam noodles were produced by replacing high-gluten wheat flour with yam flour modified with plasma-activated water and twin-screw extrusion (PAW-TSE). The effects of varying amounts of modified yam flour on the color, cooking characteristics, texture, and in vitro digestibility of the noodles were investigated. As the amount of modified yam flour increased, the noodles became darker in color, while the bound water content increased, and the free water content decreased. The modified yam flour also affected the cooking properties, reducing the optimal cooking time, decreasing the water absorption, and increasing the cooking loss. Textural analysis revealed that the addition of modified yam flour improved the texture of raw noodles, enhancing their elasticity and chewiness after cooking, thus providing a better eating experience. Furthermore, the modified yam flour increased the resistant starch content, thereby enhancing the nutritional value of the noodles. These findings provide valuable insights for food manufacturers seeking to develop healthier and more appealing noodle products, potentially leading to greater consumer acceptance and market success.